Improvement of Mother Knowledge Who Have Children Age 2-5 Years About Training Toilet Using a Drawing Media (International Journal of Studies in Nursing, 2019)
Toilet training in children is an attempt to train children to be able to control urination and defecation. The purpose of this study was to find out the development of pictorial media as a learning method for mothers in training toilet training in children aged 2-5 years in the Work Area of Bolo Health Center, Bolo District, Bima Regency. The design of this study is “Pretest-Posttest, Control Group Design”. The object of the study was 80 mothers who had children aged 2 - 5 years. Data were taken using the checklist sheet. To find out the results of the development of pictorial media as a learning method for mothers in training toilet training in children aged 2-3 years, the Wilcoxon test was performed by statistical tests. The results showed that the knowledge of mothers before toilet training through pictorial media was 29 people (72.5%) lacked the knowledge and 11 people (27.5%) had enough knowledge, after training, there were significant changes, 37 people (92.5) good knowledge and 3 people (7.5%) enough knowledge. The conclusion of the pictorial media development training can increase maternal knowledge about toilet training in children aged 2-5 years in the Work Area of Bolo Community Health Center, Bolo District, Bima Regency.